2017
DOI: 10.1136/oemed-2017-104531
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial job stressors and suicidality: a meta-analysis and systematic review

Abstract: This study provides some evidence that job stressors may be related to suicidal outcomes. However, as most studies in the area were cross-sectional and observational in design, there is a need for longitudinal research to assess the robustness of observed associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
143
2
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(170 citation statements)
references
References 51 publications
15
143
2
10
Order By: Relevance
“…The authors1 reported that high psychological job demands increased the risk for suicide death in the original paper by Ostry et al 2: OR=1.32 (95% CI: 1.31 to 1.33). They also reported a gender difference in their meta-analysis that high psychological job demands were significantly and positively associated with suicide death in male workers (OR=1.20, 95% CI: 1.10 to 1.31).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…The authors1 reported that high psychological job demands increased the risk for suicide death in the original paper by Ostry et al 2: OR=1.32 (95% CI: 1.31 to 1.33). They also reported a gender difference in their meta-analysis that high psychological job demands were significantly and positively associated with suicide death in male workers (OR=1.20, 95% CI: 1.10 to 1.31).…”
mentioning
confidence: 95%
“…I read with great interest the meta-analysis paper by Milner et al 1 about the associations between psychosocial job stressors and suicidality in working populations. The authors have compiled  and investigated 22 epidemiological studies on chronic job stressors (job control, job demands, job strain, colleague/supervisor support, effort – reward imbalance, job insecurity, role conflict and working hours/shift work) and suicide ideation/death in the literature, which is a very timely and important review that will contribute to the primary prevention of suicide in working populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive analysis of work-related suicide has been lacking, and addressing this gap in the present number of Occupational and Environmental Medicine, Milner and colleagues carried out the first systematic review and meta-analysis on the association between job stressors and suicidality 5. They used psychosocial factors at work as a broad concept to describe work-related stress exposures.…”
mentioning
confidence: 99%
“…In the meta-analysis published by Milner et al in the present number,5 a total of 22 studies were included after the systematic literature searches. They were located in Germany, Norway, South Korea, the USA, France, China (Hong Kong Special Administrative Region), Australia, Canada, Italy, South Korea and Sweden.…”
mentioning
confidence: 99%